Early death in Munchausen syndrome: A case report. Issue 8 (20th June 2019) - Di Lorenzo, Rosaria; Lannocca, Ludovica; Burattini, Maritea; Vasta, Andrea; Galletti, Martina; Minarini, Alessandro; Mongelli, Francesca; Sportiello, Salvatore; Rovesti, Sergio; Ferri, Paola
Abstract: This case contributes to raising awareness and understanding of the complex clinical presentations of Munchausen syndrome (MS). Education of staff to the seriousness and genuineness of this disorder should be implemented, especially in hospital units, in order to detect such complex clinical situations quickly and accurately, preventing iatrogenic risks. Abstract : This case contributes to raising awareness and understanding of the complex clinical presentations of Munchausen syndrome (MS). Education of staff to the seriousness and genuineness of this disorder should be implemented, especially in hospital units, in order to detect such complex clinical situations quickly and accurately, preventing iatrogenic risks.